Laminate
Patent Information
- Application Number
- JP2026055698
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2026-03-30
- Publication Date
- 2026-10-14
AI Technical Summary
【0008】 本発明によれば、正極、セパレータ、及び負極を含む積層体において、イオン導電性と、セパレータと電極の接着強度と、を両立することができる。
Smart Images

Figure 2026167616000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a laminate. [Background technology]
[0002] In a battery cell, in a laminate including a positive electrode, a separator, and a negative electrode, it is being considered to provide a composite layer containing inorganic particles and a binder resin in the separator.
[0003] Patent Document 1 describes a separator that includes a substrate and a composite layer of ceramic particles and an adhesive polymer formed on the substrate. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Chinese Patent Application Publication No. 114665226 Specification [Overview of the Initiative] [Problems that the invention aims to solve]
[0005] When the above composite layer is provided on the separator, ionic conductivity improves, but the adhesive strength between the separator and the electrode decreases, which could potentially reduce the reliability of the battery cell.
[0006] One example of the object of the present invention is to achieve both ionic conductivity and adhesive strength between the separator and the electrode in a laminate including a positive electrode, a separator, and a negative electrode. [Means for solving the problem]
[0007] According to the present invention, the following laminate is provided. [1] A laminate comprising a positive electrode having a positive electrode active material layer, a negative electrode having a negative electrode active material layer, and a separator located between the positive electrode and the negative electrode, Between the positive electrode and the separator, and between the negative electrode and the separator, there is a composite layer containing an inorganic filler and a granular binder resin. A laminate having an inorganic layer and an adhesive layer between the positive electrode and the separator, and between the negative electrode and the separator on the other side. [2] With respect to 100% by mass of the composite layer, The content of the binder resin is 10% by mass or more and 40% by mass or less. [1] The laminate described above. [3] The content of the binder resin in the composite layer is 0.1 times or more and 1.0 times or less than the content of the inorganic filler. The laminate described in [1] or [2]. [4] The space between the positive electrode and the separator, and the space between the negative electrode and the separator, are the space between the positive electrode and the separator. A laminate according to any one of [1] to [3]. [5] The surface roughness Sa of the separator-side surface of the positive electrode active material layer is 0.3 μm or more and 3.0 μm or less. A laminate according to any one of [1] to [4]. [6] The surface roughness Sa of the separator-side surface of the negative electrode active material layer is 1.0 μm or more and 5.0 μm or less. A laminate according to any one of [1] to [5]. [7] The resistivity is between 2.0 Ω·cm and 5.0 Ω·cm. A laminate according to any one of [1] to [6]. [8] At least one of the peel strengths between the positive electrode active material layer and the separator, and between the negative electrode active material layer and the separator, is 1.2 N or more and 4.0 N or less. A laminate according to any one of [1] to [7]. [9] The average particle size of the binder resin is 0.5 μm or more and 4.0 μm or less. The laminate according to any one of claims 1 to 8. Effects of the Invention
[0008] According to the present invention, in a laminate including a positive electrode, a separator, and a negative electrode, both ionic conductivity and the adhesive strength between the separator and the electrode can be achieved. Brief Description of the Drawings
[0009] [Figure 1] This is a schematic diagram of the laminate according to the present embodiment. [Figure 2] This is a schematic diagram of the composite layer according to the present embodiment. Modes for Carrying Out the Invention
[0010] Hereinafter, embodiments of the present invention will be described with reference to the drawings. In all the drawings, the same constituent elements are denoted by the same reference numerals, and redundant descriptions are omitted as appropriate.
[0011] [Laminate] Figure 1 shows an outline of the laminate according to the present embodiment. The laminate according to the present embodiment is a laminate including a positive electrode 30 having a positive electrode active material layer, a negative electrode 20 having a negative electrode active material layer, and a separator 10 positioned between the positive electrode 30 and the negative electrode 20, wherein one of the portion between the positive electrode 30 and the separator 10 and the portion between the negative electrode 20 and the separator 10 is provided with a composite layer 11 containing an inorganic filler and a granular binder resin, and the other of the portion between the positive electrode 30 and the separator 10 and the portion between the negative electrode 20 and the separator 10 is provided with a layer (insulating layer) 12 containing an inorganic substance and an adhesive layer 13. The laminate according to the present embodiment includes the separator 10, the negative electrode 20, and the positive electrode 30. Further, the composite layer 11 is formed on one surface of the separator 10. In addition, the insulating layer 12 is formed on one surface of the separator 10, and the adhesive layer 13 is further formed on the surface of the layer (insulating layer) 12 containing an inorganic substance opposite to the separator 10. The negative electrode 20 includes a negative electrode active material layer and a negative electrode current collector. The positive electrode 30 includes a positive electrode active material layer and a positive electrode current collector.
[0012] The resistivity of the laminate in this embodiment is preferably 2.0 Ω·cm or more and 5.0 Ω·cm or less. Specifically, the resistivity of the laminate can be measured by the method described in the example.
[0013] Furthermore, in the laminate of this embodiment, preferably, at least one of the peel strengths between the positive electrode active material layer and the separator, and between the negative electrode active material layer and the separator, is 1.2 N or more and 4.0 N or less, and more preferably, both the peel strength between the positive electrode active material layer and the separator, and the peel strength between the negative electrode active material layer and the separator, are 1.2 N or more and 4.0 N or less. Specifically, the peel strength between the positive electrode active material layer and the separator, and the peel strength between the negative electrode active material layer and the separator can be measured by the method described in the example.
[0014] The details of each configuration are described below.
[0015] <Separator 10> Examples of separators include porous separators. Examples of separator forms include membranes, films, and nonwoven fabrics. Examples of porous separators include polyolefin-based porous separators such as polypropylene-based and polyethylene-based; porous separators formed from polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride hexafluoropropylene copolymer, etc.
[0016] The thickness of the separator is not particularly limited, but is preferably 5 μm to 25 μm, and more preferably 7 μm to 15 μm.
[0017] <Composite layer 11> As described above, a composite layer 11 is formed on one side of the separator. Preferably, the composite layer 11 is located between the positive electrode 30 and the separator 10. The composite layer 11 includes an inorganic filler and granular binder resin 11a. It may further include a binder resin B for bonding the inorganic filler and the granular binder resin 11a. In the composite layer 11, the binder resin 11a includes, for example, a granular material with an average particle size larger than that of the inorganic filler. The composite layer 11 according to this embodiment is prepared, for example, as follows. First, a binder resin solution is prepared by dissolving the binder resin 11a in a mixed solvent consisting of a solvent that dissolves the binder resin 11a (hereinafter also referred to as a "good solvent") and a solvent that does not dissolve the binder resin 11a (hereinafter also referred to as a "poor solvent"), and dispersing the inorganic filler as well. An example of a good solvent is ethanol, and an example of a poor solvent is water. As an example, the ratio of the poor solvent to the good solvent is 60% to 85% by mass of the poor solvent and 15% to 40% by mass of the good solvent. After coating one side of the separator substrate with this solution, the separator is immersed in a solidification solution consisting of a mixed solvent and water, which is an example of a poor solvent. By including granular material with an average particle size larger than that of the inorganic filler, the binder resin 11a forms a three-dimensional network structure, and larger granular binder resin 11a than that of the inorganic filler can be left behind. Furthermore, the composite layer 11 can be obtained by washing the solidification solution with water and drying the water.
[0018] The inorganic filler described above includes, for example, one or more selected from the group consisting of highly heat-resistant oxides, nitrides, sulfides, and carbides, preferably one or more selected from the group consisting of oxide-based ceramics such as titania, alumina, boehmite, silica, magnesia, zirconia, zinc oxide, iron oxide, ceria, and yttria, and more preferably one or more selected from the group consisting of titania, alumina, boehmite, and silica.
[0019] The average particle size D50 of the inorganic filler contained in the composite layer 11 is preferably 0.005 μm or more and 10.0 μm or less, and preferably 0.01 μm or more and 5.0 μm or less. Furthermore, the average particle size D50 of the inorganic filler is preferably 0.01 μm or larger. Also, the average particle size D50 of the inorganic filler is preferably 0.7 μm or smaller.
[0020] The binder resin 11a above includes, for example, one or more selected from the group consisting of polyvinyl alcohol, polyacrylic acid, carboxymethylcellulose, polytetrafluoroethylene, polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVdF), styrene-butadiene rubber, and polyimide.
[0021] The average particle size of the binder resin 11a contained in the composite layer 11 is preferably 0.3 μm or more and 4.0 μm or less, and preferably contains binder resin 11a with a particle size of 0.3 μm or more and 3.0 μm or less. The average particle size of the binder resin 11a contained in the composite layer can be calculated, for example, by measuring the particle size of 50 particles from an SEM image of the cross-section of the composite layer and taking their average value. Furthermore, the average particle size of the binder resin 11a is preferably 0.5 μm or larger. Also, the average particle size of the binder resin 11a is preferably 3.0 μm or smaller.
[0022] Furthermore, the binder resin B may include, for example, one or more selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer, carboxymethylcellulose, and styrene-butadiene rubber.
[0023] The composite layer 11 can be formed, for example, by applying and drying a slurry in which the inorganic filler and binder resin 11a are dispersed in an organic solvent. More specifically, it is as follows. First, at least a portion of binder resin B is added to the mixed solvent of the poor solvent and good solvent described above, and the mixture is heated to a temperature of 40°C to 60°C and left for 0.5 hours to 1.5 hours to dissolve binder resin B. Subsequently, the inorganic filler and the remaining binder resin B are added, and the mixture is stirred at room temperature (22°C to 25°C), at a rpm of 2000 rpm to 3000 rpm, for 0.5 hours to 1.0 hour. Next, the binder resin 11a is added and the mixture is stirred at room temperature (22°C to 25°C), at a rpm of 40 rpm to 60 rpm for 5 to 15 minutes. The slurry obtained in this way is applied to a separator, pre-dried at 58°C to 62°C for 10 minutes, and then dried at 78°C to 82°C for 2 hours. The coated layer is then solidified by immersion in a coagulation solution mixed with water and dimethylacetamide, and then washed with water to form a composite layer containing an inorganic filler and a binder resin. Each material is selected so that the binder resin 11a maintains the particle size described above.
[0024] Figure 2 is an enlarged view of the composite layer 11. As shown in Figure 2, the composite layer 11 contains a mixture of inorganic filler 11b and granular binder resin 11a.
[0025] The inorganic filler content in the composite layer 11 is preferably 50% to 90% by mass, preferably 60% to 90% by mass, and more preferably 70% to 90% by mass, based on 100% by mass of the entire composite layer. Furthermore, the content of the binder resin 11a in the composite layer 11 is preferably 5% by mass or more and 40% by mass or less, and more preferably 5% by mass or more and 20% by mass or less, based on 100% by mass of the entire composite layer. This content is also preferably 10% by mass or more and 40% by mass or less, and more preferably 15% by mass or more and 30% by mass or less. The binder resin 11a may be used in particulate (powder) form, or it may be prepared in solution or emulsion form. The viscosity of the emulsion-formed binder can be appropriately adjusted according to the desired thickness and porosity. Furthermore, the content of binder resin B in the composite layer 11 is preferably 0.5% by mass or more, and preferably 15% by mass or less, based on 100% by mass of the total inorganic filler.
[0026] The content of the binder resin 11a in the composite layer 11 is preferably 0.1 times or more and 1.0 times or less than the content of the inorganic filler.
[0027] The thickness of the composite layer 11 is not particularly limited, but is preferably 0.5 μm or more and 5.0 μm or less, and more preferably 1.0 μm or more and 4.0 μm or less.
[0028] <Layer containing inorganic material (insulating layer) 12> As described above, an inorganic layer (insulating layer) 12 is formed on one side of the separator 10. The insulating layer 12 prevents the positive and negative electrodes from coming into direct physical contact when the lithium-ion battery malfunctions and the separator melts due to high temperatures in the laminate. When the battery is charging and discharging normally, this layer allows ions such as lithium and sodium to pass through. The insulating layer 12 according to this embodiment is formed as follows. First, a binder resin solution is prepared by dissolving the binder resin in a mixed solvent consisting of a good solvent that dissolves the binder resin and a poor solvent that does not dissolve the binder resin, and by dispersing an inorganic filler. This solution is coated onto one side of the separator substrate, which is a side different from the composite layer, and then immersed in a solidification solution consisting of the mixed solvent and water, which is an example of a poor solvent. After that, the binder resin is solidified into a three-dimensional network structure, the solidification solution is washed off with water, and the water is dried. In this way, the insulating layer 12 can be obtained.
[0029] An example of the insulating layer 12 described above is a ceramic layer. The ceramic layer that becomes the insulating layer 12 can be formed, for example, by applying a paste obtained by dispersing or dissolving an inorganic filler and a binder resin in any solvent to one side of the separator and drying it. The ceramic layer may also contain other auxiliary agents. In the ceramic layer, the inorganic fillers are partially bonded to each other by the binder resin after drying, and the separator and inorganic particles are partially bonded to each other by the binder resin, while pores are formed in the gaps where inorganic particles, separators, and binder resin are not present, allowing the electrolyte to penetrate.
[0030] The inorganic filler described above includes, for example, one or more selected from the group consisting of highly insulating oxides, nitrides, sulfides, and carbides, preferably one or more selected from the group consisting of oxides such as titania, alumina, boehmite, silica, magnesia, zirconia, zinc oxide, iron oxide, ceria, and yttria, and more preferably one or more selected from the group consisting of titania, boehmite, alumina, and silica. This further improves heat resistance. In addition, this reduces thermal shrinkage of the separator and further suppresses short circuits between electrodes.
[0031] The average particle size D50 of the inorganic filler contained in the insulating layer 12 is preferably 0.005 μm or more and 10.0 μm or less, and preferably 0.01 μm or more and 8.0 μm or less. Here, the average particle size D50 refers to the particle size at 50% of the cumulative value in the particle size distribution (volume basis) measured by laser diffraction scattering.
[0032] The above-mentioned binder resin comprises, for example, one or more selected from the group consisting of polyvinyl alcohol, polyacrylic acid, carboxymethylcellulose, polytetrafluoroethylene, polyvinylidene fluoride (PVdF), styrene-butadiene rubber, and polyimide, preferably comprising one or more selected from the group consisting of PVdF and styrene-butadiene rubber, and more preferably comprising PVdF.
[0033] The above ceramic layer-forming material may further contain a thickening agent to ensure fluidity suitable for coating.
[0034] The above-mentioned thickener is not particularly limited as long as it is a thickener that can be used in lithium-ion batteries, but can be selected from the group consisting of, for example, cellulosic polymers such as carboxymethylcellulose (CMC), methylcellulose, hydroxypropylcellulose and their ammonium salts and alkali metal salts, water-soluble polymers such as polycarboxylic acids, polyethylene oxide, polyvinylpyrrolidone, polyacrylates, and polyvinyl alcohol.
[0035] The solvent used in the ceramic layer-forming material described above is not particularly limited, and known solvents can be used as appropriate. For example, one or more solvents selected from the group consisting of N-methyl-2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO), dimethylformamide (DMF), and water can be used.
[0036] From the viewpoint of improving the balance of mechanical strength, handling properties, and lithium-ion conductivity, the thickness of the insulating layer is preferably 1 μm to 20 μm, and more preferably 1 μm to 12 μm.
[0037] <Adhesive layer 13> The adhesive layer 13 according to this embodiment is manufactured, for example, as follows. First, a binder resin solution is prepared by dissolving and dispersing the binder resin in a mixed solvent consisting of a good solvent that dissolves the binder resin and a poor solvent that does not dissolve it. This solution is applied to one side of the insulating layer 12, a side different from the side on which the separator is formed, and then the separator is immersed in a solidification solution consisting of the mixed solvent and water, which is an example of a poor solvent. After that, the binder resin is solidified into a three-dimensional network structure, the solidification solution is washed off with water, and the water is dried. In this way, the adhesive layer 13 can be obtained. The formation pattern of the adhesive layer is not particularly limited; it may be uniform, patterned, or irregularly shaped. The type of adhesive is not particularly limited, but examples include fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyvinyl fluoride (PVF); conductive polymers such as polyanilines, polythiophenes, polyacetylenes, and polypyrroles; synthetic rubbers such as styrene-butadiene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), and acrylonitrile-butadiene rubber (NBR); water-soluble resins such as polyvinylpyrrolidone; or polysaccharides such as carboxymethylcellulose (CMC), xanthan gum, guar gum, and pectin; and acrylic resins such as acrylates and methacrylates. Methods for applying the adhesive include, but are not limited to, die application, comma application, lip application, transfer application, gravure application, inkjet application, doctor blade application, and screen printing.
[0038] The thickness of the adhesive layer 13 is preferably 1 μm to 20 μm, and more preferably 1 μm to 12 μm, from the viewpoint of improving the balance of mechanical strength, handling properties, and lithium ion conductivity.
[0039] <Negative electrode 20> The negative electrode of this embodiment includes a negative electrode active material layer. The negative electrode active material layer of this embodiment may, for example, include a negative electrode active material and further include one or more selected from the group consisting of a negative electrode binder resin and a conductive additive.
[0040] Examples of the negative electrode active material of the present embodiment include carbon materials such as natural graphite, artificial graphite, hard carbon, and soft carbon; metals capable of occluding lithium, such as silicon and tin, and alloys or oxides thereof; composites of silicon and porous carbon; lithium-based metals such as lithium metal and lithium alloys; and conductive polymers such as polyacene and polyacetylene. As the negative electrode active material, only one type may be used alone, or two or more types may be used in combination. The negative electrode active material of the present embodiment preferably contains graphite and silicon, and the silicon is preferably SiO x (0<x≦2), Si / C containing Si-C composite particles including silicon and a carbon material, and one or two or more selected from the group consisting of Si, more preferably SiO x (0<x≦2), and one or two or more selected from the group consisting of Si / C containing Si-C composite particles including silicon and a carbon material, further preferably containing Si / C containing Si-C composite particles including silicon and a carbon material. In the composite of silicon and porous carbon of the present embodiment, the carbon material includes a porous carbon material, and silicon is present in at least a part of the pores of the porous carbon material.
[0041] Examples of the conductive aid in the negative electrode active material layer of the present embodiment include carbon fibers such as carbon nanofibers; carbon blacks such as acetylene black and Ketjen black; and carbon materials such as activated carbon, mesoporous carbon, fullerenes, and carbon nanotubes. One of these may be used alone, or two or more thereof may be used in combination. Among these, the conductive aid in the negative electrode active material layer of the present embodiment preferably contains a carbon material, more preferably contains carbon nanotubes, and further preferably contains single-walled carbon nanotubes, from the viewpoint of further improving the performance balance between the energy density and cycle characteristics of the obtained lithium ion secondary battery.
[0042] The content of the negative electrode active material in the negative electrode active material layer of the present embodiment is preferably 80 mass% to 98 mass%, more preferably 85 mass% to 98 mass%, and even more preferably 88 mass% to 98 mass%, when the total amount of the negative electrode active material layer is taken as 100 mass%.
[0043] Examples of binder resins in the negative electrode active material layer of this embodiment include fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyvinyl fluoride (PVF); polycarboxylic acid polymers such as poly(meth)acrylic acid; conductive polymers such as polyaniline, polythiophene, polyacetylene, and polypyrrole; synthetic rubbers such as styrene-butadiene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), and acrylonitrile-butadiene rubber (NBR); and polysaccharides such as carboxymethylcellulose (CMC), xanthan gum, guar gum, and pectin. One of these may be used alone, or two or more may be used in combination. Among these, the binder in the negative electrode active material layer of this embodiment preferably contains one or more selected from the group consisting of fluororesin, polycarboxylic acid polymer, and synthetic rubber, from the viewpoint of further improving the battery performance of the stacked lithium-ion secondary battery, more preferably contains one or more selected from the group consisting of polyvinylidene fluoride, polycarboxylic acid polymer, and styrene-butadiene rubber, even more preferably contains a polycarboxylic acid polymer, and even more preferably contains poly(meth)acrylic acid. Such a negative electrode binder resin may be in emulsion form.
[0044] The binder resin content in the negative electrode active material layer of this embodiment may be, for example, 1% to 8% by mass, or 2% to 5% by mass, when the total amount of the negative electrode active material layer is considered to be 100% by mass.
[0045] The negative electrode active material layer can appropriately use electrode additives commonly used for electrode formation, such as thickeners, dispersants, and stabilizers.
[0046] The density of the negative electrode active material layer in this embodiment is preferably 1.0 g / cm³. 3 More than 3.0g / cm 3 More preferably, 1.2 g / cm³ 3More than 2.0g / cm 3 The following applies:
[0047] Furthermore, the surface roughness Sa of the separator-side surface of the negative electrode active material layer is preferably between 1.0 μm and 5.0 μm, and more preferably between 1.5 μm and 5.0 μm. The surface roughness is measured using a 3D shape measuring machine (KEYENCE VR-3000).
[0048] The thickness of the negative electrode active material layer in this embodiment is preferably 1 μm to 150 μm, more preferably 5 μm to 100 μm, and even more preferably 10 μm to 80 μm.
[0049] The negative electrode of this embodiment may further include a negative electrode current collector. The negative electrode current collector may include, for example, one or more materials selected from the group consisting of copper, stainless steel, nickel, titanium, and alloys thereof. The shape of the negative electrode current collector may be, for example, foil, plate, or mesh. The thickness of the negative electrode current collector is, for example, between 1 μm and 50 μm.
[0050] The negative electrode according to this embodiment can be manufactured, for example, by the following procedure. First, a slurry containing a negative electrode active material, binder resin, and conductive additive dispersed in an organic solvent is applied to part or all of the surface of a negative electrode current collector such as copper foil, and dried to obtain a negative electrode precursor sheet. The obtained negative electrode precursor sheet can then be compressed using press molding methods such as a roll press, uniaxial press, rubber press, or isotropic and isobaric press (CIP method, WIP method) to obtain a negative electrode sheet. N-methylpyrrolidone or water can be used as the organic solvent.
[0051] <Positive electrode 30> The positive electrode of this embodiment includes a positive electrode active material layer. The positive electrode active material layer of this embodiment may further include, for example, one or more selected from the group consisting of a positive electrode active material, a positive electrode binder resin, and a conductive additive.
[0052] The positive electrode active material in this embodiment is not particularly limited and includes, for example, lithium and transition metal composite oxides such as lithium-nickel composite oxide, lithium-cobalt composite oxide, lithium-manganese composite oxide, lithium-nickel-manganese composite oxide, lithium-nickel-cobalt composite oxide, lithium-nickel-aluminum composite oxide, lithium-nickel-cobalt-aluminum composite oxide, lithium-nickel-cobalt-manganese composite oxide, lithium-nickel-manganese-aluminum composite oxide, lithium-nickel-cobalt-manganese-aluminum composite oxide; transition metal sulfides such as TiS2, FeS, MoS2; and MnO, V2O5, V6O 13 The material comprises one or more selected from the group consisting of transition metal oxides such as TiO2 and olivine-type lithium phosphate oxide, and preferably comprises a lithium composite oxide having a layered rock salt-type crystal structure, more preferably comprising one or more selected from the group consisting of lithium-nickel composite oxide, lithium-cobalt composite oxide, lithium-nickel-aluminum composite oxide, and lithium-nickel-cobalt-manganese composite oxide, and even more preferably comprising lithium-nickel-cobalt-manganese composite oxide. Here, the olivine-type lithium phosphate oxide includes, for example, at least one element from the group consisting of Mn, Cr, Co, Cu, Ni, V, Mo, Ti, Zn, Al, Ga, Mg, B, Nb, and Fe, as well as lithium, phosphorus, and oxygen.
[0053] The average particle diameter D50 of the positive electrode active material in this embodiment is preferably 0.1 μm or more and 30 μm or less, more preferably 0.3 μm or more and 20 μm or less, even more preferably 0.5 μm or more and 15 μm or less, and even more preferably 1.0 μm or more and 10.0 μm or less. Here, the average particle diameter D50 refers to the particle diameter at 50% of the cumulative value in the particle size distribution (volume basis) measured by laser diffraction scattering.
[0054] Examples of binder resins for the positive electrode active material in this embodiment include fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyhexafluoropropylene (PHFP), polyvinyl fluoride (PVF), or copolymers of VdF-hexafluoropropylene; conductive polymers such as polyanilines, polythiophenes, polyacetylenes, and polypyrroles; synthetic rubbers such as styrene-butadiene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), and acrylonitrile-butadiene rubber (NBR); and polysaccharides such as carboxymethylcellulose (CMC), xanthan gum, guar gum, and pectin. One of these may be used alone, or two or more may be used in combination. Among these, the binder in the positive electrode active material layer of this embodiment preferably comprises one or more selected from the group consisting of fluororesin, polycarboxylic acid polymer, and synthetic rubber, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, more preferably comprises one or more selected from the group consisting of polyvinylidene fluoride, polycarboxylic acid polymer, and styrene-butadiene rubber, and even more preferably comprises polyvinylidene fluoride.
[0055] The content of the positive electrode binder resin in the positive electrode active material layer of this embodiment is preferably 0.1% by mass or more and 10.0% by mass or less, more preferably 0.2% by mass or more and 9.0% by mass or less, even more preferably 0.5% by mass or more and 8.0% by mass or less, and even more preferably 0.8% by mass or more and 5.0% by mass or less, when the total content of the positive electrode active material layer is considered to be 100% by mass.
[0056] Examples of conductive additives in the positive electrode active material layer of this embodiment include carbon fibers such as carbon nanofibers; carbon blacks such as acetylene black and Ketjenblack; and carbon materials such as activated carbon, mesoporous carbon, fullerenes, and carbon nanotubes. One of these may be used alone, or two or more may be used in combination.
[0057] When the total mass of the positive electrode active material layer of the present embodiment is taken as 100% by mass, the content of the conductive aid in the positive electrode active material layer is preferably 0.1% by mass to 10.0% by mass, more preferably 0.15% by mass to 9.0% by mass, still more preferably 0.18% by mass to 8.5% by mass, still more preferably 0.20% by mass to 7.5% by mass, and still more preferably 0.20% by mass to 7.0% by mass, from the viewpoint of improving the battery characteristics of the lithium ion secondary battery.
[0058] The density of the positive electrode active material layer of the present embodiment is preferably 2.5 g / cm 3 or more and 4.0 g / cm 3 or less, more preferably 3.0 g / cm 3 or more and 4.0 g / cm 3 or less.
[0059] Further, the surface roughness Sa of the surface of the positive electrode active material layer on the separator side is preferably 0.3 μm to 3.0 μm, and more preferably 0.5 μm to 2.5 μm. The surface roughness Sa is measured by Keyence VR-3000.
[0060] The thickness of the positive electrode active material layer is not particularly limited, but for example, it is preferably 1 μm to 150 μm, more preferably 5 μm to 100 μm, and still more preferably 10 μm to 80 μm.
[0061] The positive electrode of the present embodiment may further include a positive electrode current collector. The positive electrode current collector contains, for example, one or two or more selected from the group consisting of aluminum, stainless steel, nickel, titanium and alloys thereof. The shape of the positive electrode current collector may be, for example, a foil, a flat plate or a mesh. The thickness of the positive electrode current collector is, for example, 1 μm to 50 μm.
[0062] The positive electrode of this embodiment can be manufactured, for example, by dissolving or dispersing the components constituting the positive electrode active material layer in a solvent to produce a positive electrode slurry, applying the positive electrode slurry to at least one surface of the positive electrode current collector, and then drying and rolling it. A roll press is preferably used for rolling, and the rolling pressure is preferably 500 kg / cm or more and 10,000 kg / cm or less, more preferably 1,000 kg / cm or more and 8,000 kg / cm or less, and even more preferably 1,000 kg / cm or more and 6,000 kg / cm or less.
[0063] The present invention is not limited to the embodiments described above, and any modifications or improvements that can achieve the objectives of the present invention are included within the scope of the present invention. [Examples]
[0064] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples.
[0065] [Example 1] The laminate was manufactured using the following method.
[0066] <Fabrication of the negative electrode> A negative electrode active material slurry was prepared by adding an appropriate amount of water to a solid component consisting of a negative electrode active material, a binder resin, and a conductive additive. Next, the negative electrode active material slurry was applied to a 6 μm thick copper foil, which served as the negative electrode current collector, with an initial charge capacity of 4.3 mAh / cm² per unit area. 2 After applying the material in the desired amount, it was dried to obtain a negative electrode laminate. Next, using a roll press, the negative electrode laminate was processed to a density of 1.65 g / cm³. 3 The negative electrode was obtained by pressing with a pressure such that the following occurred. • Negative electrode active material: A mixture of silicon-carbon composite (Si / C) and graphite in a ratio of 15:85, containing 97 parts by mass. • Binder resin: Styrene-butadiene rubber, content 2.5 parts by mass • Conductive additive: Single-walled carbon nanotubes, content 0.5 parts by mass
[0067] <Fabrication of the positive electrode> A positive electrode active material slurry was prepared by adding an appropriate amount of N-methyl-2-pyrrolidone to a solid component consisting of positive electrode active material, binder resin, and conductive additive. Next, the positive electrode active material slurry was applied to a 12 μm thick aluminum foil, which served as the positive electrode current collector, with an initial charge capacity of 4.0 mAh / cm² per unit area. 2 After applying the material in the amount specified above, it was dried. Next, using a roll press, the density of the dried positive electrode active material layer was determined to be 3.5 g / cm³ per side of the positive electrode current collector foil. 3 The positive electrode was obtained by pressing it with a pressure such that it would result in a positive electrode. ·Cathode active material: Li(Ni) 0.9 Co 0.05 Mn 0.05 )O2, content 98 parts by mass • Binder resin: Polyvinylidene fluoride, content 1.5 parts by mass • Conductive additive: Multilayer carbon nanotubes, content 0.5 parts by mass
[0068] <Fabrication of composite layer - separator - insulating layer - adhesive layer> <Formation of an insulating layer on the separator> An inorganic filler and a binder resin were mixed and dispersed in a mixed solvent of dimethylacetamide and water to obtain a slurry with a binder resin concentration of 5% by mass. This slurry was applied to one side of a 12 μm thick microporous polyethylene film to be used as a separator and dried. This film was then immersed in a coagulation solution mixed with water and dimethylacetamide to solidify the coating layer. After washing with water and drying, a porous insulating layer was formed on one side of the separator. • Inorganic filler: Boehmite, content 84% by mass • Binder resin: Polyvinylidene fluoride (PVdF), content 16% by mass
[0069] <Formation of an adhesive layer on the insulating layer> A polyvinylidene fluoride (PVdF) solution is prepared by dissolving it in a solvent made by mixing dimethylacetamide, a good solvent for dissolving polyvinylidene fluoride resins, and water, which does not dissolve polyvinylidene fluoride resins. This solution is applied to the surface of the insulating layer, and then immersed in a solidification solution made by mixing water and dimethylacetamide in a 7:3 ratio to solidify it and obtain a polyvinylidene fluoride resin layer with a three-dimensional network structure. This is then washed with water and dried to obtain an adhesive layer.
[0070] <Formation of composite layer on separator> Water and ethanol were mixed in a mass ratio of 8:2, and then carboxymethylcellulose (CMC), which is binder resin B, was added at a solid content ratio of 1.0% by mass. The mixture was heated to 50°C and left for 1 hour to dissolve binder resin B and obtain a slurry. To the obtained slurry, 80% by mass of inorganic filler and 4.0% by mass of the remaining binder resin B, styrene-butadiene rubber, were added in solid content ratio, and the mixture was stirred at 25°C and 2500 rpm for 30 minutes. Then, 15% by mass of binder resin 11a was added in solid content ratio, and the mixture was stirred at 25°C and 50 rpm for 10 minutes. This slurry was applied to the side of the microporous polyethylene film, which served as the separator, that did not have an insulating layer, and after pre-drying at 60°C for 10 minutes, it was subjected to main drying at 80°C for 2 hours. The coated layer was solidified by immersion in a coagulation solution mixed with water and dimethylacetamide, and then washed with water to obtain a porous composite layer containing inorganic filler and binder resin. • Inorganic filler: Ceramic particles, 80% by mass • Binder resin 11a: Polymethyl methacrylate (PMMA), content 15% by mass Binder resin B: Styrene-butadiene rubber, 4% by mass content, and carboxymethylcellulose (CMC), 1% by mass content, total 5% by mass.
[0071] <Laminate fabrication and hot pressing process> A laminate was fabricated by placing a separator between the positive and negative electrodes, and the electrodes and separator were bonded together by dry hot pressing. At this time, the positive electrode side was in contact with a composite layer containing inorganic filler and granular binder resin with an average particle size larger than that of the inorganic filler, while the negative electrode side was in contact with a layer containing inorganic material (insulating layer) and an adhesive layer. The hot pressing conditions were 80°C, 3 MPa, and 2 minutes.
[0072] <Fabrication of non-aqueous secondary batteries> A lithium-ion secondary battery was fabricated by placing the fabricated electrode stack and non-aqueous electrolyte inside a laminated casing made from a film primarily composed of aluminum, joining the positive and negative electrodes via positive and negative tabs respectively, and sealing the laminated casing. The lithium-ion battery was then charged at 0.5C of its capacity, and after the upper voltage limit reached 4.2V, it was charged at a constant voltage until the total charging time was 12 hours. Next, it was discharged at 0.5C of its capacity at a constant current until the lower voltage limit reached 2.5V. Then, it was charged again under the same conditions, left in a constant temperature bath at 45°C for 3 days, and discharged again under the same conditions.
[0073] [Example 2] The laminate was manufactured in the same manner as in Example 1, except that polyacrylic acid was used as the binder resin for forming the negative electrode active material layer.
[0074] [Example 3] The laminate was manufactured in the same manner as in Example 1, except that the pressing pressure was different.
[0075] [Comparative Example 1] The configuration of the separator-composite layer-positive electrode laminate in Example 1 was changed to a separator-insulating layer-adhesive layer-positive electrode laminate to obtain a negative electrode-adhesive layer-insulating layer-separator-insulating layer-adhesive layer-positive electrode laminate. The formation of the insulating layer and adhesive layer in the separator-insulating layer-adhesive layer-positive electrode laminate was carried out under the same conditions as the formation of the insulating layer and adhesive layer in the negative electrode-adhesive layer-insulating layer-separator-composite layer-positive electrode laminate in Example 1.
[0076] [Comparative Example 2] The configuration of the laminate in Example 1, consisting of a negative electrode-adhesive layer-insulating layer-separator-composite layer-positive electrode, was changed to a configuration of a negative electrode-composite layer-separator-composite layer-positive electrode, thereby obtaining a negative electrode-composite layer-separator-composite layer-positive electrode laminate. The formation of the composite layer in the negative electrode-composite layer-separator-composite layer-positive electrode was carried out under the same conditions as the formation of the composite layer in the separator-composite layer-positive electrode laminate in Example 1.
[0077] In the laminates of each example and comparative example, the surface roughness Sa of one separator side of the positive electrode active material layer and the negative electrode active material layer was measured. The measurement results are shown in Table 1. The measurement conditions for surface roughness Sa were as follows: Surface roughness was measured non-contact using a Keyence VR-3000 tester. Measurements were taken within a 100 μm × 100 μm area. All tests were performed at 25°C.
[0078] [evaluation] The laminates of each example and comparative example were evaluated as follows.
[0079] <Resistivity> The resistivity was measured for the laminates of each example and comparative example. The measurement results are shown in Table 1. The resistivity measurement conditions were as follows: A Solartron SI 1287 electrochemical interface and an SI 1255B frequency response analyzer were controlled by CorrWare and Zplot, and EIS measurements were performed. EIS was measured potentiostatically at SOC 50%, with AC oscillations of 10mV amplitude at frequencies from 100kHz to 0.1Hz. EIS data were fitted using ZView software. Specifically, the obtained Nyquist plots were fitted using an equivalent circuit to calculate the bulk resistance R. Using this R, the effective cross-sectional area A and thickness L of the laminate were used to calculate the resistivity using the formula: ρ = R × A / L. All tests were performed at 22°C.
[0080] <Electrode peel strength> For each example and comparative example, the peel strength between the negative electrode active material layer and the separator, and the peel strength between the positive electrode active material layer and the separator were measured for the laminates. The measurement results are shown in Table 1. The measurement conditions for peel strength were as follows. The samples used were laminates in which a positive or negative electrode and a separator were bonded together, cut to a width of 15 mm and a length of 50 mm. The samples were prepared semi-dry and stored in Lamizip®. Immediately before measurement, the samples were removed from Lamizip and measured in air using an Imada SL-6001 tensile and compression tester. When peeling off the separator, a bonded section of 15 mm in width and 25 mm in length was left in the center of the laminate. The separator was fixed to the lower jig installed on the tester, and one end of the electrode from which the separator had been peeled off was fixed to the upper jig. The tensile speed was set to 100 mm / min.
[0081] [Table 1]
[0082] In summary, the laminate according to this embodiment was found to have lower resistivity and superior ionic conductivity compared to Comparative Example 1, which was a laminate consisting of a negative electrode, adhesive layer, insulating layer, separator, insulating layer, adhesive layer, and positive electrode. Furthermore, while Comparative Example 2, a laminate consisting of a negative electrode, composite layer, separator, composite layer, and positive electrode, had an unmeasurable low peel strength on the negative electrode side and an unstable contact surface on the negative electrode, the laminate according to this embodiment had a sufficiently high peel strength on the negative electrode side and a stable contact surface on the negative electrode. [Explanation of Symbols]
[0083] 10 Separators 11 Composite layer 11a Granular binder resin 11b Inorganic filler 12. Layer containing inorganic materials (insulating layer) 13 Adhesive layer 20 negative electrode 30 positive electrode
Claims
1. A laminate comprising a positive electrode having a positive electrode active material layer, a negative electrode having a negative electrode active material layer, and a separator located between the positive electrode and the negative electrode, Between the positive electrode and the separator, and between the negative electrode and the separator, there is a composite layer containing an inorganic filler and a granular binder resin. A laminate having an inorganic layer and an adhesive layer between the positive electrode and the separator, and between the negative electrode and the separator on the other side.
2. With respect to 100% by mass of the composite layer, The content of the binder resin is 10% by mass or more and 40% by mass or less. The laminate according to claim 1.
3. The content of the binder resin in the composite layer is 0.1 times or more and 1.0 times or less than the content of the inorganic filler. The laminate according to claim 1 or 2.
4. The space between the positive electrode and the separator, and the space between the negative electrode and the separator, are the space between the positive electrode and the separator. The laminate according to claim 1 or 2.
5. The surface roughness Sa of the separator-side surface of the positive electrode active material layer is 0.3 μm or more and 3.0 μm or less. The laminate according to claim 1 or 2.
6. The surface roughness Sa of the separator-side surface of the negative electrode active material layer is 1.0 μm or more and 5.0 μm or less. The laminate according to claim 1 or 2.
7. The resistivity is between 2.0 Ω·cm and 5.0 Ω·cm. The laminate according to claim 1 or 2.
8. At least one of the peel strengths between the positive electrode active material layer and the separator, and between the negative electrode active material layer and the separator, is 1.2 N or more and 4.0 N or less. The laminate according to claim 1 or 2.
9. The average particle size of the binder resin is 0.5 μm or more and 4.0 μm or less. The laminate according to claim 1 or 2.
Citation Information
Patent Citations
Adhesive diaphragm and preparation method thereof
CN114665226A